Pelatihan Relaksasi Otot Progresif untuk Mengurangi Stres Pengasuh - Martaria Rizky Rinaldi; Natasya Natasya (Humanitas (Jurnal Psikologi), 2025)
Caregiving for individuals with mental illness poses various challenges that can disrupt the well-being of the families providing care. Caregivers are vulnerable to experiencing stress. This research aims to determine the effectiveness of progressive muscle relaxation in reducing stress among caregivers of families with mental illness. The research design employed is a quasi-experiment with a one-group pre-test-post-test design. The participants in the study include 4 family members who care for individuals with mental illness. Participants were selected based on interviews and their willingness to participate. Data collection involved pre-test and post-test phases using the Kingston Caregiver Stress Scale. Data analysis was conducted using the Wilcoxon signed-rank test method. The data analysis results show a significant decrease in stress (p < 0.05). These findings indicate that progressive muscle relaxation is effective in reducing stress among caregivers of families with mental illness. Therefore, progressive muscle relaxation can be utilized for managing stress in caregivers of families with mental illness.